2013
DOI: 10.1097/pgp.0b013e31828cb0be
|View full text |Cite
|
Sign up to set email alerts
|

Primary Squamous Cell Carcinoma of the Endometrium

Abstract: Molecular alterations leading to cell cycle dysregulation in primary squamous cell carcinoma of the endometrium (PSCCE) and correlation with clinical outcome are incompletely described. Molecular variables of 5 cases of PSCCE were compared with 8 controls of endometrial endometrioid adenocarcinoma and correlated with overall survival. Immunohistochemical expression of pRB, p18, p19, CDK4, CDK6, Cyclin D1, p16, HPVE7, pTEN, ER, PR, and p53 was independently scored (intensity: 0-3 and proportion: 0-5) twice by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…A total of 28 cases was identified in 14 studies (Table 4). 4,5,[7][8][9][10][11][12][13][14][15][16][17][18] The median age at diagnosis was 62 years, which is slightly younger than the women in our study (mean and median, 78 y). The majority of cases were negative for ER and PR in 19/23 (82.6%) and 19/22 (86.4%) cases, respectively.…”
Section: Fluhmann Criterion: a Simultaneous Cervical Scc Should Be Ab...mentioning
confidence: 83%
“…A total of 28 cases was identified in 14 studies (Table 4). 4,5,[7][8][9][10][11][12][13][14][15][16][17][18] The median age at diagnosis was 62 years, which is slightly younger than the women in our study (mean and median, 78 y). The majority of cases were negative for ER and PR in 19/23 (82.6%) and 19/22 (86.4%) cases, respectively.…”
Section: Fluhmann Criterion: a Simultaneous Cervical Scc Should Be Ab...mentioning
confidence: 83%
“…A study conducted by Bures et al suggested that PSCCE exhibits molecular alterations involving the pRB-cyclin D1-CDK4/6-p16 pathway and pTEN. [9] Compared with type I endometrial carcinoma, PSCCE has a unique pathogenesis. [9] No evidence of squamous metaplasia, atypical hyperplasia, or HPV infection was found in our patient, and no cancer was found in the mucosa or stroma of the cervical canal.…”
Section: Discussionmentioning
confidence: 99%
“…Total hysterectomy with bilateral salpingo-ovariectomy is the first-line treatment of choice, especially for postmenopausal women [2, 4, 8]. The efficacy of radiotherapy and chemotherapy as adjuvant therapies remains highly controversial [12, 13]. Epidermoid carcinoma has a poor prognosis compared with adenocarcinoma of the endometrium [12].…”
Section: Discussionmentioning
confidence: 99%